YO AUTOBIOGRÁFICO Y FIGURA(S) DE AUTOR EN LA TÍA JULIA Y EL ESCRIBIDOR Y EL PEZ EN EL AGUA DE MARIO VARGAS LLOSA. - NEGRETE SANDOVAL, JULIA ÉRIKA (Nueva Revista de Filología Hispánica, 2019)
Convinced that behind the scenes of all writing it is possible to discern the writer's self-affirmation and (im)posture, and since studies on "authoriality" in Hispanic American literature continue to be on the rise, I propose to study the forms of autofiguration in Mario Vargas Llosa's La tía Julia y el escribidor and El pez en el agua. The autobiographical nature of both books encompasses fundamental ideas about the author and authorship, that take the form of textual images that ask questions about who the writer is and what she/he ought to be.